2017
DOI: 10.3390/bs7030057
|View full text |Cite
|
Sign up to set email alerts
|

In Their Own Words: How Family Carers of People with Dementia Understand Resilience

Abstract: There is a growing body of research on resilience in family carers of people with dementia, but carers’ voices are noticeably absent from it. The aim of this study was to explore carers’ definitions of resilience and their opinions on the factors associated with resilience. Twenty-one in-depth interviews were conducted in Australia with people who were currently, or had previously been, caring for a family member with dementia. Transcripts were analysed thematically and three themes emerged: the presence of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 42 publications
(90 reference statements)
6
39
0
1
Order By: Relevance
“…Some viewpoints consider the entire process of caring as adversity, while other studies position the common negative outcomes reported by carers of PWD—carer burden, depression, anxiety, burn‐out, stress, lower levels of well‐being, and so forth—as the adversity which family carers must adapt to or overcome . In order to demonstrate positive adaptation, Luthar and colleagues posit that the positive adaptation must be considered and defined in the context of the adversity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some viewpoints consider the entire process of caring as adversity, while other studies position the common negative outcomes reported by carers of PWD—carer burden, depression, anxiety, burn‐out, stress, lower levels of well‐being, and so forth—as the adversity which family carers must adapt to or overcome . In order to demonstrate positive adaptation, Luthar and colleagues posit that the positive adaptation must be considered and defined in the context of the adversity.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Throughout the literature on family carers of PWD, the conceptualisation of the term "adversity" varies considerably. O'Dwyer 21 proposes that adversity is different for each individual carer, and adversity can be acute or cumulative, depending on individual and life course experiences. Some viewpoints consider the entire process of caring as adversity, 22,23 while other studies position the common negative outcomes reported by carers of PWD-carer burden, depression, anxiety, burn-out, stress, lower levels of well-being, and so forth-as the adversity which family carers must adapt to or overcome.…”
mentioning
confidence: 99%
“…Research around the world namely show that most of caretaking for PWD is carried out by PWD relatives, mostly by their family members [35][36][37]. Their crucial role is to help PWD remain in home care as long as possible [37].…”
Section: Discussionmentioning
confidence: 99%
“…Their crucial role is to help PWD remain in home care as long as possible [37]. This often represents for them an extensive burden because PWD should not be left alone and without control [35][36][37][38]. When facing these issues, relatives of PWD are significantly assisted by programmes of the associations Spominčica which, in Slovenia, have been importantly contributed to form a friendly environment for PWD and their relatives.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses ran in three phases, first, to meet objective one, to explore discrepancies and congruency between definitions of resilience in the academic literature and carers own conceptualisations, interview data were analysed using a framework (Ritchie, Spencer, & O'Connor, ). ID takes a ‘flexible approach’ avoiding restrictive line by line coding.…”
Section: Methodsmentioning
confidence: 99%